Application of Dare Program for Increased Capabilities of Teenagersin Preventing Drug Abuse Through in Medan - Wahyuni, Sri Eka; Daulay, Wardiyah; Nst, Mahnum Lailan (Talenta Publisher Universitas Sumatera Utara, 2018)
Teenagers are a group of humans who are vulnerable to the drug. It is all because of teenagers age have the process of seeking self of identity and focusing on the group's friends. This activity has done in Sari Rejo, Medan Polonia. Medan Polonia is the second area of higher drugs consumption in Medan. DARE Program (Drug Abuse Resistance Education) is one program that has proven effective as an intervention to prevent drug abuse for teenagers. This program is carried out by forming peer educators and then training cognitive, affective and psychomotor peer educator skills to prevent drug abuse. Teenagers can expressly reject the invitation of group friends or their peers to try to consume drugs.The results showed the affective and psychomotor capabilities of teenagers are different pre and post DARE Program (p=0,000, p-value 0,000). It is recommended that the overall DARE Program is carried out in order to improve the abilities of teenagers to prevent drug abuse.